Fibule en Iran. Collection de M. Foroughi - Ghirshman, Roman
Fibules protohistoriques: A. Amlach; В. Luristan; Fibules de l’époque achéménide et sassanide: A. Deilaman: B. Kermanchah; Fibules romaines: A. Deilaman; B. Kermanchah.